2005
DOI: 10.1007/s10450-005-5990-8
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Chromatography and Crystallization for Efficient Separations of Isomers

Abstract: Within the pharmaceutical industry and in biotechnology there is an increasing need for selective and efficient separation technologies to isolate and purify value-added products. A hybrid process approach combining chromatography and fractional crystallization is studied below. The work presented is concerned with the application and evaluation of this concept in order to isolate a certain pharmaceutical intermediate from a binary mixture. A comparison with performing the same separation exclusively in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Multiobjective optimization of productivity and evaporation cost in terms of essential operating parameters (column length and SMB feed concentration) shows for this coupled process an optimum SMB purity value as a trade-off between increased SMB performance and recycle of the mother liquor. Further examples devoted to study quantitatively combinations of chromatography and crystallization were reported in [306][307][308] . All the results summarized here clearly indicate that the combined process can achieve better performance than the SMB process alone.…”
Section: Coupling Of Chromatography and Crystallizationmentioning
confidence: 99%
“…Multiobjective optimization of productivity and evaporation cost in terms of essential operating parameters (column length and SMB feed concentration) shows for this coupled process an optimum SMB purity value as a trade-off between increased SMB performance and recycle of the mother liquor. Further examples devoted to study quantitatively combinations of chromatography and crystallization were reported in [306][307][308] . All the results summarized here clearly indicate that the combined process can achieve better performance than the SMB process alone.…”
Section: Coupling Of Chromatography and Crystallizationmentioning
confidence: 99%
“…The SMB technology was a breakthrough in increasing the productivity of chromatographic separations; however, a significative decrease in productivity can still be observed as the level of purification increases. For this reason, some authors have been pursuing the use of hybrid processes, combining SMB chromatography and crystallization in order to obtain an increase in productivity (Lim et al, 1995;Lorenz et al, 2001;Bléhaut et al, 2001;Gedicke, 2005;Lorenz et al, 2006). The general concept of the hybrid process is based on using chromatography as a prepurification stage, followed by a crystallization step to achieve the final purification.…”
Section: Enantioseparation Via Chromatography and Crystallizationmentioning
confidence: 99%
“…The present paper is part of a project to establish the feasibility and limitations of such a hybrid chromatography-crystallization process [12].…”
Section: Introductionmentioning
confidence: 99%